2020
DOI: 10.2147/ijn.s231538
|View full text |Cite
|
Sign up to set email alerts
|

<p>Regulation of ERK1/2 and SMAD2/3 Pathways by Using Multi-Layered Electrospun PCL–Amnion Nanofibrous Membranes for the Prevention of Post-Surgical Tendon Adhesion</p>

Abstract: Background: Adhesion after tendon injury is a common complication in clinical practice. The lack of effective prevention mechanisms seriously affects the functional rehabilitation of patients. This research aimed to optimise the amniotic membrane and explain the mechanism of tendon-amniotic membrane by imitating the tendon sheath to construct a multilayer electrospun polycaprolactone (PCL) nanofibre membrane. Materials and Methods: Fresh amnions were subjected to freezing and vacuum drying. The two surfaces of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 48 publications
(42 reference statements)
0
41
0
Order By: Relevance
“…TGF-β is one of the most important cytokines involved in tendon regeneration and tissue adhesion (Liu et al, 2019). Moreover, TGF-β enhances collagen synthesis and fibroblast proliferation via the extracellular signal-regulated kinase 2/SMAD pathway (Liu C. et al, 2020), and increased collagen levels in turn stimulate tendon regeneration. Importantly, TGF-β can localize to repaired tendon sites, resulting in increased collagen synthesis and tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β is one of the most important cytokines involved in tendon regeneration and tissue adhesion (Liu et al, 2019). Moreover, TGF-β enhances collagen synthesis and fibroblast proliferation via the extracellular signal-regulated kinase 2/SMAD pathway (Liu C. et al, 2020), and increased collagen levels in turn stimulate tendon regeneration. Importantly, TGF-β can localize to repaired tendon sites, resulting in increased collagen synthesis and tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrophilic angles of freeze-dried amnion and nanofiber membrane were 51.18° ± 2.72° and 59.44° ± 4.15°, respectively. The maximum modulus of elasticity of the nanofiber membrane was higher than that of the freeze-dried amnion, and the tensile strength and toughness of the nanofiber membrane were higher than those of the freeze-dried amnion [ 25 ]. The nanofibrous membranes were sterilized with UV radiation before use [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The PCL-amnion nanofibrous membrane had better mechanical strength and biocompatibility. In a previous study, we found that an electrospun PCL-amnion nanofibrous membrane effectively prevented post-surgical tendon adhesion and promoted tendon healing [25]. Although there is a number of studies that report on the application of amniotic membranes in nerve repair, they are not yet widely used in the clinic [24,35].…”
Section: Plos Onementioning
confidence: 99%
“…Lately, multilayered approaches have gained attention as novel methods for scaffold design. [ 191,192 ] Different layer‐by‐layer techniques such as simultaneous wet electrospinning and cell‐seeding, alternating layers of nanofibers and microfibers, varying polymers, or arranging electrospun layers coated with hydrogels have been developed. [ 193–195 ] Systems combining electrospun fibrous mats with woven/knitted constructs in multilayered scaffolds have been recently explored for tendon and ligament engineering.…”
Section: Fiber‐based Engineered Scaffolds For Tendons and Ligamentsmentioning
confidence: 99%